Correlations between Chemistry Lab Notebooks Scores and Academic Achievement Scores of Gifted Science Students and Their Perceptions on Chemistry Lab and the Lab Notebooks - Kim, Dong-Jin; Park, Kuk-Tae; Pentland, Denise (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
The purpose of this study is to analyze chemistry laboratory notebooks completed by gifted science students and their observations on chemistry experiments and the laboratory notebooks, focusing on the correlations among the students mid-term academic achievement (MAA) scores, the holistic grading scale (HGS) and lab note rubric (LNR) scores for their chemistry laboratory notebooks. Through an e-mail questionnaire, the gifted science students, now attending universities, gave their opinion on the value of the chemistry experiments and the laboratory notebooks they wrote in their high school days. Based on the correlations between the students mid-term scores and their chemistry experiment laboratory notebook scores, the students were divided into four groups and one student from each group was selected for a semi-structured telephone interview. The results of the study revealed that the MAA scores and chemistry LNR scores are more correlated than the MAA scores and chemistry HGS scores and the students from every group felt that they gained a better understanding of experimental procedures and data analysis by doing laboratory experiments. All of them think that completing the chemistry laboratory notebook in science high school and university is very useful for studies in advanced chemistry.